Large increase in stretchability of organic electronic materials by encapsulation. (September 2016) - Sawyer, Eric J.; Zaretski, Aliaksandr V.; Printz, Adam D.; de los Santos, Nathaniel V.; Bautista-Gutierrez, Alejandra; Lipomi, Darren J.
Abstract: This paper describes a large increase in the stretchability–i.e., resistance to cracking under tensile deformation–of organic semiconductor films produced by encapsulation. Specifically, encapsulation is shown to greatly suppress crack formation and growth in films of materials relevant to organic solar cells. Encapsulated films of the organic bulk heterojunction blend of poly(3-heptylthiophene) and phenyl-C 61 -butyric acid methyl ester (P3HpT:PCBM) exhibit greater crack-onset strain, lower crack density, and lower average crack length than unencapsulated films. Films of P3HpT:PCBM on polyurethane (PU) showed cracks at 6.6 ± 0.5% without encapsulation and 40 ± 4% with encapsulation. Films of the conductive polymer poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) also demonstrate suppressed cracking when encapsulated, as well as reduced dependence of resistance on strain after the crack-onset strain (which indicates a greater usable range of strain for encapsulated vs. unencapsulated films). A finite element model is used to explain the mechanism suppressing crack growth, which involves delocalization of strain around minor defects in the films by the encapsulating substrate. In addition, encapsulation is used to enable the first encapsulated solar cell in which every component is intrinsically stretchable. These cells are stretchable to 9–10% strain, with some cells performing well even after their crack-onset strain of 8–9%, whereas unencapsulated cells fail at 4% strain. This work highlights the necessity to consider encapsulation–already important for protecting the electronically active components of a device from abrasion, weathering, or chemical damage–as an important factor in the mechanical robustness of stretchable devices. Graphical abstract: Highlights: Encapsulating organic thin-films improves stretchability by suppressing cracking. Model shows encapsulation delocalizes strain around film defects. First solar cell with intrinsic stretchability in all components is demonstrated.